2010
DOI: 10.1159/000319015
|View full text |Cite
|
Sign up to set email alerts
|

Robot Therapy: A New Approach for Mental Healthcare of the Elderly – A Mini-Review

Abstract: Mental healthcare of elderly people is a common problem in advanced countries. Recently, high technology has developed robots for use not only in factories but also for our living environment. In particular, human-interactive robots for psychological enrichment, which provide services by interacting with humans while stimulating their minds, are rapidly spreading. Such robots not only simply entertain but also render assistance, guide, provide therapy, educate, enable communication, and so on. Robot therapy, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
223
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(236 citation statements)
references
References 66 publications
2
223
0
11
Order By: Relevance
“…Social robots such as animallike robot companions are increasingly being used in health care (e.g., Wada and Shibata, 2007;Shibata and Wada, 2010;Bemelmans et al, 2012Bemelmans et al, , 2013Kachouie et al, 2014). Research shows that interaction with animallike robots can have positive effects similar to those from interaction with real animals (e.g., Eachus, 2001;Wada and Shibata, 2007;Banks et al, 2008;Bernabei et al, 2013;Robinson et al, 2015;Sefidgar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social robots such as animallike robot companions are increasingly being used in health care (e.g., Wada and Shibata, 2007;Shibata and Wada, 2010;Bemelmans et al, 2012Bemelmans et al, , 2013Kachouie et al, 2014). Research shows that interaction with animallike robots can have positive effects similar to those from interaction with real animals (e.g., Eachus, 2001;Wada and Shibata, 2007;Banks et al, 2008;Bernabei et al, 2013;Robinson et al, 2015;Sefidgar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that interaction with animallike robots can have positive effects similar to those from interaction with real animals (e.g., Eachus, 2001;Wada and Shibata, 2007;Banks et al, 2008;Bernabei et al, 2013;Robinson et al, 2015;Sefidgar et al, 2016). Moreover, robots have advantages compared to real animals: their behavior can be better controlled; they do not carry diseases; and they need less care (Eachus, 2001;Filan and Llewellyn-Jones, 2006;Shibata and Wada, 2010). These advantages are especially important when working with a vulnerable population such as the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such example is the use of a seal robot named Paro which was designed for use with the elderly [29]. As an accompaniment and social stimulator to individuals with dementia living in long-term care facilities, its integrated sensors allow it to interact in various ways when it is touched.…”
Section: Other Media Used In the Area Of Dementiamentioning
confidence: 99%
“…Recently, some investigations suggested that a pet robot provided the human with a good effect, e.g., reduction of stress hormones [22] [23], improvement of brain functioning [24], and positive psychological effects in social relationships [25] [26]. A communication robot is further expected to engender mental effects, such as pleasure and relaxation [27].…”
Section: Introductionmentioning
confidence: 99%